2013
DOI: 10.1021/pr3009836
|View full text |Cite
|
Sign up to set email alerts
|

Apoe, Mbl2, and Psp Plasma Protein Levels Correlate with Diabetic Phenotype in NZO Mice—An Optimized Rapid Workflow for SRM-Based Quantification

Abstract: Male New Zealand Obese (NZO) mice progress through pathophysiological stages similar to humans developing obesity-associated type 2 diabetes (T2D). The current challenge is to establish quantitative proteomics from small plasma sample amounts. We established an analytical workflow that facilitates a reproducible depletion of high-abundance proteins, has high throughput applicability, and allows absolute quantification of proteins from mouse plasma samples by LC-SRM-MS. The ProteoMiner equalizing technology was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 73 publications
2
35
0
Order By: Relevance
“…Sample preparation for MS Plasma samples were depleted from highly abundant proteins and proteolysed with trypsin as previously described [27]. All samples were randomly distributed into one of three batches for processing, and the experimenters were blinded to the sample-group allocation during the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Sample preparation for MS Plasma samples were depleted from highly abundant proteins and proteolysed with trypsin as previously described [27]. All samples were randomly distributed into one of three batches for processing, and the experimenters were blinded to the sample-group allocation during the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma depletion and on-bead digestions using ProteoMiner beads Depletion and tryptic digestion of plasma samples which had been stored at −80°C were performed as previously described in six processing batches [12]. For quality control of depletion, digestion and MS measurements, a final concentration of 50 fmol ribulose-1,5-bisphosphate carboxylase oxygenase protein (RuBisCO; Sigma-Aldrich, Taufkirchen, Germany) was spiked into each 10 μl plasma sample as an internal standard (see ESM methods section 'Quality control of sample preparation and MSmeasurement').…”
Section: Srm-ms Measurementsmentioning
confidence: 99%
“…Candidate protein selection Candidate proteins were obtained from a previous pilot mouse study [12] and unpublished mouse data (von Toerne and Hauck, data not shown). These were complemented by results from shotgun measurements of human plasma samples from different sources (data not shown).…”
Section: Srm-ms Measurement and Quantification Principlementioning
confidence: 99%
See 2 more Smart Citations